Stem cambial variants of the Clematis species (Ranunculaceae) in Taiwan - Sheng-Zehn Yang (National Taiwan University, 2021)
Studies on cambial variants of Taiwanese species from the genus Clematis (Ranunculaceae) are scarce. This study aimed to investigate and compare the patterns of secondary growth in stems of 22 Clematis taxa, including 19 species and three varieties. The experimental results showed that approximately 27% of the Clematis species in Taiwan had 12 vascular bundles in the stem. In three cambial variants of the genus, the stem was characterized by an irregular conformation, axial vascular elements in segments, and a wedge-like phloem. The rhytidome is composed of periderm and non-conducting phloem and forms either cogwheel-like or continuous segment bark. Eight Clematis species formed arc-like bark, which developed the cogwheel-like rhytidome. Most Clematis species had an indentation in the region of the wider rays, and the wedge-like indentations developed in the interfascicular region of C. henryi var. morii and C. pseudootophora. Narrow rays that occurred in the secondary xylem increased with increasing stem diameter. The vessels dispersed throughout the stem were semi-ring-porous in most species but ring-porous in others. No species had diffuse porous vessels. The vessel restriction pattern was only found in the two species, C. psilandra and C. tsugetorum. The primary xylem ring was located around the pith of C. uncinata var. uncinata, making its pith cavity hexagonal in shape. Five species had the pith cavity feature. This study provides important basic information about Clematis lianas and addresses their taxonomy, which will help to understand their morphology and to ensure the conservation of their diversity.